The Use of Interferon Beta and Glatiramer Acetate in Multiple Sclerosis - Goodin, Douglas S. (Seminars in Neurology, 2013)
The modern era of the therapy for multiple sclerosis began in the 1990s with introduction of interferon beta and glatiramer acetate. Now 20 years since the introduction of these disease modifying therapies, several alternatives have become available. Although, in many cases, these new agents seem especially effective, there is little head-to-head trial data to actually compare the efficacy of the newer agents to that of the older. Moreover, there is no doubt that these older agents are both effective and very safe - something which has not always proven true about the newer therapies. Consequently, there will continue to be a place for these injectable treatments, even as we move into an era where physicians are confronted with many treatment possibilities.
Keywords: multiple sclerosis; interferon beta; glatiramer acetate